2013
DOI: 10.1124/dmd.113.053017
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cytochrome P450 Isoforms Are Involved in the Generation of a Pharmacologically Active Thiol Metabolite, whereas Paraoxonase 1 and Carboxylesterase 1 Catalyze the Formation of a Thiol Metabolite Isomer from Ticlopidine

Abstract: Ticlopidine is a first-generation thienopyridine antiplatelet drug that prevents adenosine 59-diphosphate (ADP)-induced platelet aggregation. We identified the enzymes responsible for the two-step metabolic bioactivation of ticlopidine in human liver microsomes and plasma. Formation of 2-oxo-ticlopidine, an intermediate metabolite, was NADPH dependent and cytochrome P450 (CYP) 1A2, 2B6, 2C19, and 2D6 were involved in this reaction. Conversion of 2-oxo-ticlopidine to thiol metabolites was observed in both micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Consistent with previous report, 19) clopidogrel was found to be an inhibitor of CES1 with an IC 50 value of 24.7 µM on PNPA hydrolysis (Fig. 4).…”
Section: Resultssupporting
confidence: 80%
“…Consistent with previous report, 19) clopidogrel was found to be an inhibitor of CES1 with an IC 50 value of 24.7 µM on PNPA hydrolysis (Fig. 4).…”
Section: Resultssupporting
confidence: 80%
“…35, 36 Ticlopidine is subject to extensive metabolism by several cytochrome P450 isoforms and carboxyesterase. 37 A study in rats suggests that adducts are formed following metabolism by cytochrome P450 with evidence for toxicity after biliary excretion of glutathione-conjugated metabolites via MRP2-facilitated transport. 38 In previous studies, 22 Japanese patients with ticlopidine DILI showed an association with an HLA haplotype including A*33:03 (odds ratio 13).…”
Section: Discussionmentioning
confidence: 99%
“…The fragmentation pattern and increased retention time compared to ticlopidine suggested that metabolite M5 was an N‐oxide. Based on the fragmentation pattern and literature, M6 was most likely 2‐oxoticlopidine . Metabolites M4–M6 were abundant in both S9 fraction incubations and in the BMO incubations.…”
Section: Resultsmentioning
confidence: 89%
“…Based on the fragmentation pattern and literature, M6 was most likely 2-oxoticlopidine. [18] Metabolites M4-M6 were abundant in both S9 fraction incubations and in the BMO incubations. M5 was produced with very high abundance in the BMO incubations.…”
Section: Ticlopidinementioning
confidence: 91%